Abnormalities of Aspiration and Swallowing Function in Survivors of Acute Respiratory Failure - Langmore, Susan E.; Krisciunas, Gintas P.; Warner, Heather; White, S. David; Dvorkin, Daniel; Fink, Daniel; McNally, Edel; Scheel, Rebecca; Higgins, Carrie; Levitt, Joseph E.; McKeehan, Jeffrey; Deane, Sandra; et al. (Dysphagia, 2020)
The mechanisms responsible for aspiration are relatively unknown in patients recovering from acute respiratory failure (ARF) who required mechanical ventilation. Though many conditions may contribute to swallowing dysfunction, alterations in laryngeal structure and swallowing function likely play a role in the development of aspiration. At four university-based tertiary medical centers, we conducted a prospective cohort study of ARF patients who required intensive care and mechanical ventilation for at least 48 h. Within 72 h after extubation, a Fiberoptic Flexible Endoscopic Evaluation of Swallowing (FEES) examination was performed. Univariate and multivariable analyses examined the relationship between laryngeal structure and swallowing function abnormalities. Aspiration was the primary outcome, defined as a Penetration- Aspiration Scale (PAS) score of 6 or greater. Two other salient signs of dysphagia—spillage and residue—were secondary outcomes. A total of 213 patients were included in the final analysis. Aspiration was detected in 70 patients (33%) on at least one bolus. The most commonly aspirated consistency was thin liquids (27%). In univariate analyses, several abnormalities in laryngeal anatomy and structural movement were significantly associated with aspiration, spillage, and residue. In a multivariable analysis, the only variables that remained significant with aspiration were pharyngeal weakness (Odds ratio = 2.57, 95%CI = 1.16–5.84, p = 0.019) and upper airway edema (Odds ratio = 3.24, 95%CI = 1.44–7.66, p = 0.004). These results demonstrated that dysphagia in ARF survivors is multifactorial and characterized by both anatomic and physiologic abnormalities. These findings may have important implications for the development of novel interventions to treat dysphagia in ARF survivors. Clinical Trials Registration ClinicalTrials.gov Identifier: NCT02363686, Aspiration in Acute Respiratory FailureSurvivors. © 2020, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: Deglutition; Deglutition Disorders; Humans; Prospective Studies; Respiratory Aspiration; Respiratory Insufficiency; Survivors; acid aspiration; dept.cmd; dysphagia; human; peer-reviewed; prospective study; respiratory failure; survivor; swallowing

Correction to: Abnormalities of aspiration and swallowing function in survivors of acute respiratory failure - Langmore, Susan E.; Krisciunas, Gintas P.; Warner, Heather L.; White, S. David; Dvorkin, Daniel; Fink, Daniel S.; McNally, Edel; Scheel, Rebecca; Higgins, Carrie; Levitt, Joseph E.; McKeehan, Jeffrey; Deane, Sandra; et al. (Dysphagia, 2021)
Due to the errors occurred in the originally published version, this article is being reprinted in its entirety as Correction. All errors have been corrected. It is the correct version. © 2021, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: dept.cmd; erratum; peer-reviewed

Development of an Accurate Bedside Swallowing Evaluation Decision Tree Algorithm for Detecting Aspiration in Acute Respiratory Failure Survivors - Moss, Marc; White, S. David; Warner, Heather; Dvorkin, Daniel; Fink, Daniel; Gomez-Taborda, Stephanie; Higgins, Carrie; Krisciunas, Gintas P.; Levitt, Joseph E.; McKeehan, Jeffrey; McNally, Edel; Rubio, Alix; et al. (Chest, 2020)
Background: The bedside swallowing evaluation (BSE) is an assessment of swallowing function and airway safety during swallowing. After extubation, the BSE often is used to identify the risk of aspiration in acute respiratory failure (ARF) survivors. Research Question: We conducted a multicenter prospective study of ARF survivors to determine the accuracy of the BSE and to develop a decision tree algorithm to identify aspiration risk. Study Design and Methods: Patients extubated after ≥ 48 hours of mechanical ventilation were eligible. Study procedures included the BSE followed by a gold standard evaluation, the flexible endoscopic evaluation of swallowing (FEES). Results: Overall, 213 patients were included in the final analysis. Median time from extubation to BSE was 25 hours (interquartile range, 21-45 hours). The FEES was completed 1 hour after the BSE (interquartile range, 0.5-2 hours). A total of 33% (70/213; 95% CI, 26.6%-39.2%) of patients aspirated on at least one FEES bolus consistency test. Thin liquids were the most commonly aspirated consistency: 27% (54/197; 95% CI, 21%-34%). The BSE detected any aspiration with an accuracy of 52% (95% CI, 45%-58%), a sensitivity of 83% (95% CI, 74%-92%), and negative predictive value (NPV) of 81% (95% CI, 72%-91%). Using recursive partitioning analyses, a five-variable BSE-based decision tree algorithm was developed that improved the detection of aspiration with an accuracy of 81% (95% CI, 75%-87%), sensitivity of 95% (95% CI, 90%-98%), and NPV of 97% (95% CI, 95%-99%). Interpretation: The BSE demonstrates variable accuracy to identify patients at high risk for aspiration. Our decision tree algorithm may enhance the BSE and may be used to identify patients at high risk for aspiration, yet requires further validation. Trial Registry: ClinicalTrials.gov; No.: NCT02363686; URL: www.clinicaltrials.gov; © 2020 American College of Chest Physicians
Keywords: Airway Extubation; Algorithms; Article; Decision Trees; Deglutition; Female; Humans; Male; Point-of-Care Testing; Predictive Value of Tests; Reproducibility of Results; Respiration, Artificial; Respiratory Aspiration; Respiratory Insufficiency; Risk Assessment; Survivors; Symptom Assessment; United States; acid aspiration; acute respiratory failure; adult; adverse event; aged; algorithm; artificial ventilation; aspiration; bedside swallowing evaluation; clinical trial; controlled study; decision tree; dept.cmd; diagnostic accuracy; diagnostic test accuracy study; digestive system examination; dysphagia; epidemiology; extubation; female; flexible endoscopic evaluation of swallowing; gastrointestinal endoscopy; high risk patient; human; intubation; major clinical study; male; multicenter study; oxygen; oxygen therapy; pathophysiology; peer-reviewed; point of care testing; predictive value; priority journal; procedures; prospective study; pulmonary aspiration; reproducibility; respiratory failure; risk assessment; sensitivity and specificity; speech language pathologist; survivor; swallowing; symptom assessment

The Association Between Endotracheal Tube Size and Aspiration (During Flexible Endoscopic Evaluation of Swallowing) in Acute Respiratory Failure Survivors - Krisciunas, Gintas P.; Langmore, Susan E.; Gomez-Taborda, Stephanie; Fink, Daniel; Levitt, Joseph E.; McKeehan, Jeffrey; McNally, Edel; Scheel, Rebecca; Rubio, Alix C.; Siner, Jonathan M.; Vojnik, Rosemary; Warner, Heather; et al. (Critical Care Medicine, 2020)
Objectives: To determine whether a modifiable risk factor, endotracheal tube size, is associated with the diagnosis of postextubation aspiration in survivors of acute respiratory failure. Design: Prospective cohort study. Setting: ICUs at four academic tertiary care medical centers. Patients: Two hundred ten patients who were at least 18 years old, admitted to an ICU, and mechanically ventilated with an endotracheal tube for longer than 48 hours were enrolled. Interventions: Within 72 hours of extubation, all patients received a flexible endoscopic evaluation of swallowing examination that entailed administration of ice, thin liquid, thick liquid, puree, and cracker boluses. Patient demographics, treatment variables, and hospital outcomes were abstracted from the patient's medical records. Endotracheal tube size was independently selected by the patient's treating physicians. Measurements and Main Results: For each flexible endoscopic evaluation of swallowing examination, laryngeal pathology was evaluated, and for each bolus, a Penetration Aspiration Scale score was assigned. Aspiration (Penetration Aspiration Scale score ≥ 6) was further categorized into nonsilent aspiration (Penetration Aspiration Scale score = 6 or 7) and silent aspiration (Penetration Aspiration Scale score = 8). One third of patients (n = 68) aspirated (Penetration Aspiration Scale score ≥ 6) on at least one bolus, 13.6% (n = 29) exhibited silent aspiration, and 23.8% (n = 50) exhibited nonsilent aspiration. In a multivariable analysis, endotracheal tube size (≤ 7.5 vs ≥ 8.0) was significantly associated with patients exhibiting any aspiration (Penetration Aspiration Scale score ≥ 6) (p = 0.016; odds ratio = 2.17; 95% CI 1.14-4.13) and with risk of developing laryngeal granulation tissue (p = 0.02). Conclusions: Larger endotracheal tube size was associated with increased risk of aspiration and laryngeal granulation tissue. Using smaller endotracheal tubes may reduce the risk of postextubation aspiration. © 2020 International Anesthesia Research Society.
Keywords: Adult; Aged; Airway extubation; Deglutition; Deglutition disorders; Female; Humans; Intensive Care Units; Intratracheal intubation; Intubation, Intratracheal; Male; Middle Aged; Prospective Studies; Respiration, Artificial; Respiratory Aspiration; Respiratory Insufficiency; Respiratory aspiration; Respiratory distress syndrome; Risk Factors; Survivors; acid aspiration; adverse event; aged; artificial ventilation; clinical trial; dept.cmd; devices; endotracheal intubation; female; human; intensive care unit; male; middle aged; multicenter study; peer-reviewed; physiology; procedures; prospective study; respiratory failure; risk factor; survivor; swallowing

Relationship Between Laryngeal Sensation, Length of Intubation, and Aspiration in Patients with Acute Respiratory Failure. - Borders, James C; Fink, Daniel; Levitt, Joseph E; McKeehan, Jeffrey; McNally, Edel; Rubio, Alix; Scheel, Rebecca; Siner, Jonathan M; Taborda, Stephanie Gomez; Vojnik, Rosemary; Warner, Heather; White, S David; et al. (Dysphagia, 2019)
Dysphagia is common in hospitalized patients post-extubation and associated with poor outcomes. Laryngeal sensation is critical for airway protection and safe swallowing. However, current understanding of the relationship between laryngeal sensation and aspiration in post-extubation populations is limited. Acute respiratory failure patients requiring intensive care unit admission and mechanical ventilation received a Flexible Endoscopic Evaluation of Swallowing (FEES) within 72 h of extubation. Univariate and multivariable analyses were performed to examine the relationship between laryngeal sensation, length of intubation, and aspiration. Secondary outcomes included pharyngolaryngeal secretions, pneumonia, and diet recommendations. One-hundred and three patients met inclusion criteria. Fifty-one patients demonstrated an absent laryngeal adductor reflex (LAR). Altered laryngeal sensation correlated with the presence of secretions (p = 0.004). There was a significant interaction between the LAR, aspiration, and duration of mechanical ventilation. Altered laryngeal sensation was significantly associated with aspiration on FEES only in patients with a shorter length of intubation (p = 0.008). Patients with altered laryngeal sensation were prescribed significantly more restricted liquid (p = 0.03) and solid (p = 0.001) diets. No relationship was found between laryngeal sensation and pneumonia. There is a high prevalence of laryngeal sensory deficits in mechanically ventilated patients post-extubation. Altered laryngeal sensation was associated with secretions, aspiration, and modified diet recommendations especially in those patients with a shorter length of mechanical ventilation. These results demonstrate that laryngeal sensory abnormalities impact the development of post-extubation dysphagia.
Keywords: *Intubation, Intratracheal/ae [Adverse Effects]; *Laryngeal Diseases/et [Etiology]; *Pneumonia, Aspiration/et [Etiology]; *Sensation Disorders/et [Etiology]; Acute Disease; Acute respiratory failure; Article; Critical illness; Deglutition; Deglutition disorders; FEES; Female; Flexible Endoscopic Evaluation of Swallowing; Humans; Intubation, Intratracheal; Laryngeal Diseases; Laryngeal Diseases/pp [Physiopathology]; Laryngeal sensation; Larynx; Larynx/pp [Physiopathology]; Male; Middle Aged; Pneumonia, Aspiration; Prospective Studies; Respiratory Insufficiency; Sensation Disorders; Sensation Disorders/pp [Physiopathology]; Time Factors; absent laryngeal adductor reflex; acute disease; acute respiratory failure; adult; adverse event; artificial ventilation; aspiration; aspiration pneumonia; bodily secretions; clinical outcome; clinical trial; cohort analysis; controlled study; critical illness; dept.cmd; dietary intake; disease association; dysphagia; endotracheal intubation; extubation; female; hospital admission; human; intensive care; larynx; larynx disorder; lung aspiration; major clinical study; male; middle aged; multicenter study; nutritional requirement; outcome assessment; pathophysiology; peer-reviewed; pharyngolaryngeal secretions; pneumonia; prescription; prevalence; priority journal; prospective study; reflex disorder; respiratory failure; sensory dysfunction; time factor